Today I feel silly & other moods that make my day - Curtis, Jamie Lee, 1958-; Cornell, Laura (New York : Joanna Cotler Books, 1998)
A child's emotions range from silliness to anger to excitement, coloring and changing each day.
Kirkus Review
2.4
K-3.
K-3
Keywords: Toy and movable books -- Specimens; Emotions -- Fiction; Stories in rhyme; Toy and movable books; Emotions -- Fiction; Stories in rhyme; Toy and movable books